Expression Dynamics of the O-Glycosylated Proteins Recognized by Amaranthus leucocarpus Lectin in T Lymphocytes and Its Relationship With Moesin as an Alternative Mechanism of Cell Activation - Gómez-Henao, Wilton; Saavedra, Rafael; Chávez-Sánchez, Francisco Raúl; Lascurain, Ricardo; Zenteno, Edgar; Tenorio, Eda Patricia (Frontiers in Immunology, 2021)
T lymphocyte activation begins with antigen/MHC recognition by the TCR/CD3 complex followed by a costimulatory signal provided by CD28. The search for novel costimulatory molecules has been extensive due to their potential use as immunotherapeutic targets. Although some molecules have been identified, they are unable to provide sustainable signaling to allow for proper T cell activation and proliferation. It has been shown that the Amaranthus leucocarpus lectin (ALL) can be used as an in vitro costimulator of CD4+ lymphocytes in the presence of anti-CD3 mAb; this lectin specifically recognizes O-glycans of the Galβ1-3GalNAc-O-Ser/Thr type, including a 70-kDa moesin-like protein that has been suggested as the costimulatory molecule. However, the identity of this molecule has not been confirmed and such costimulation has not been analyzed in CD8+ lymphocytes. We show herein that the expression kinetics of the glycoproteins recognized by ALL (gpALL) is different in CD4+ and CD8+ T cells, unlike moesin expression. Results from IP experiments demonstrate that the previously described 70-kDa moesin-like protein is an O-glycosylated form of moesin (O-moesin) and that in vitro stimulation with anti-CD3 and anti-moesin mAb induces expression of the activation molecules CD69 and CD25, proliferation and IL-2 production as efficiently as cells costimulated with ALL or anti-CD28. Overall, our results demonstrate that O-moesin is expressed in the outer cell membrane of CD4+ and CD8+ T lymphocytes and that moesin provides a new costimulatory activation signal in both T cell subsets.